ANALISIS YURIDIS RECOVERY ASSET MELALUI TINDAK PIDANA PENCUCIAN UANG DARI HASIL TINDAK PIDANA KORUPSI - Iffana Hayu; Mukhlis R; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Eradication of criminal acts of corruption is the main agenda that must be held. Asset recoveryin corruption is the process of handling assets from the proceeds of corruption at every stage oflaw enforcement, so that the value of these assets can be maintained and returned to the state. InLaw No. 8 of 2010 Concerning the Prevention and Eradication of Money Laundering, there is apolicy related to the law on eradicating corruption and other similar laws, namely with the soleaim of narrowing down the occurrence of corruption. This means that the presence of the Law onMoney Laundering is an attempt to assist the operation of the Law on Corruption Eradication.The purpose of this study is to offer an effective and efficient strategy in returning state assetsfrom corruption through money laundering and to find out the construction of the judge's thinkingin examining and deciding money laundering cases on corruption as the predicate crime.An effective and efficient strategy in efforts to recover assets from the proceeds of corruptionthrough money laundering is to combine charges of corruption with money laundering.Accumulating criminal acts, indictments are not combined with alternative or subsidiary formsand returning assets from the proceeds of criminal acts of corruption can be carried out throughcriminal or civil instruments. The judge's thinking construction regarding evidence that has beenused in other crimes that have permanent legal force (BHT) cannot be used as evidence in othercrimes. The formulation of the crime of money laundering as a supplementary crime of corruption(predicate crime) needs to be given the same serious attention as proving that corruption is apredicate crime. The unpaid payment for the purchase of an asset becomes a consideration for thePanel of Judges that the asset is confiscated for the state.Research in making effective and efficient indictment formulations to optimally return stateassets needs to be carried out also for the future. Researchers hope that there will be more in-depth research on efforts to return state assets from the proceeds of criminal acts of corruptionthrough money laundering and other efforts as well as research in making effective and efficientindictment formulations. Efforts to return state assets outside the criminal corridor must be a moreserious concern to be carried out.Keywords: Asset Recovery, -Criminal Corruption, -Money Laundering Crimes